Characteristics of Individuals Who Underwent Cesarean Delivery After Prolonged Labor [A245]. (May 2022) - Chaiken, Sarina; Phillips, Jillian; Packer, Claire; Garg, Bharti; Caughey, Aaron
Abstract : INTRODUCTION: We sought to determine factors associated with cesarean delivery among those with prolonged labor. METHODS: We utilized linked vital statistics-patient discharge data from California (2007–2011) and included singleton non-anomalous pregnancies with a diagnosis of prolonged labor. We examined the prevalence of CD in women with prolonged labor for varying subgroups and performed multivariable logistic regression to determine factors associated with CD in those with prolonged labor. RESULTS: Among those with a diagnosis of prolonged labor (N=41, 130), 28.72% (11, 811) underwent cesarean delivery. Compared with non-Hispanic White individuals, non-Hispanic Black patients had significantly lower odds of CD (aOR, 0.88; 95% CI, 0.78–0.99), while Hispanic (aOR, 1.29; 95% CI, 1.22–1.37) or Asian persons (aOR, 1.14; 95% CI, 1.07–1.23) had higher odds of CD. As compared to those with normal BMI, being underweight (BMI<18.5) had lower odds of CD (aOR, 0.81; 95% CI, 0.72–0.91), while overweight (BMI 25–29.9; aOR, 1.33; 95% CI, 1.26–1.41) or obese (BMI ≥30; aOR, 1.87; 95% CI, 1.76–2.00) patients had higher odds of CD. Those aged ≥35 years had higher odds of CD (aOR, 1.28; 95% CI, 1.20–1.35), and patients on public insurance had lower odds of CD (aOR, 0.91; 95% CI, 0.86–0.96). CONCLUSION: Our results indicate that sociodemographic factors, including race, BMI, and age, impact odds of CD among those with prolonged labor. It is known that bias can impact decision-making in the context of labor and delivery, further attention should be placed to understand and remedy the structural causes of bias that impact who undergoes CD with prolonged labor.